2020
DOI: 10.1071/py19062
|View full text |Cite
|
Sign up to set email alerts
|

Implications for GP endorsement of a diabetes app with patients from culturally diverse backgrounds: a qualitative study

Abstract: Although many diabetes self-management apps exist, these are not tailored for people from culturally and linguistically diverse (CALD) backgrounds. This study aimed to explore GP perceptions of how diabetes app features could help GPs better support their patients from CALD backgrounds. Twenty-five semi-structured interviews with GPs in Western Sydney explored attitudes towards a proposed app’s suitability for CALD patients. Interviews were audio-recorded, transcribed and coded using Framework Analysis. Theme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Engaging patients by providing an electronic device such as a tablet for use in the practice waiting room rather than simply relying on verbal recommendations has also been explored in a feasibility study as a way of motivating patients to continue using a web-based self-regulation program once they return home [34]. Verbal recommendation by staff is one of the most widespread, routinely used methods of digital facilitation [35][36][37][38].…”
Section: Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging patients by providing an electronic device such as a tablet for use in the practice waiting room rather than simply relying on verbal recommendations has also been explored in a feasibility study as a way of motivating patients to continue using a web-based self-regulation program once they return home [34]. Verbal recommendation by staff is one of the most widespread, routinely used methods of digital facilitation [35][36][37][38].…”
Section: Promotionmentioning
confidence: 99%
“…There is some evidence that providers may be more willing and able to engage in digital facilitation efforts with patients who are already confident users of digital services, including the worried well, potentially exacerbating inequalities in access to digital health resources [71,83]. A review found that providers are more likely to recommend digital services to patients they perceive as more technologically knowledgeable, and these perceptions may be based on age, socioeconomic status, education level, and ethnic group [36,65].…”
Section: Evidence Relating To Inequality Between Different Population...mentioning
confidence: 99%
“…This research has had demonstrable benefits: by identifying the needs and preferences of patients and/or clinicans, these studies provide an evidence base for user-centred design of digital health interventions. For example, Ayre et al utilised in depth interviews with clinicans to identify specific app design needs with respect to diabetes management in culturally and linguistically diverse communities [ 12 ], while Slevin et al identified key barriers and facilitators for the use of digital health technologies to support the management of COPD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other areas of digital health, there is a growing volume of research that explores patient and/or clinician perspectives on the role of apps to support clinical care for specific health conditions e.g. [12,[13][14][15][16][17][18][19][20][21]. This research has had demonstrable benefits: by identifying the needs and preferences of patients and/or clinicans, these studies provide an evidence base for usercentred design of digital health interventions.…”
Section: Introductionmentioning
confidence: 99%